Can the Belarusian Model Provide Growth?. Issue 6 (2nd June 2016) - Zlotnikov, L.K.
Abstract : The author examines the Belarusian economic model, identifies reasons why the growth rate was statistically overstated, and analyzes some of the country's economic processes that will substantially influence its condition in the coming years.